Triple-band perfect metamaterial absorber with good operating angle polarization tolerance based on split ring arrays - Wang, Yingying; Chen, Zeqiang; Xu, Danyang; Yi, Zao; Chen, Xifang; Chen, Jian; Tang, Yongjian; Wu, Pinghui; Li, Gongfa; Yi, Yougen (Results in physics, 2020)
•The proposed absorber achieves triple-band absorption.•The proposed absorber has a good working polarization angle tolerance.•The proposed absorber are beneficial to the fabrication of the device. In this paper, a triple-band perfect metamaterial absorber based on Cu-dielectric-Cu triple-layer nanostructure is reported. The top metal film structure consists of a ring and four pairs of capacitor plates, which has a frequency selection effect, allowing the absorber to resonate in the near infrared range. Theoretical study shows that the absorption of the three absorption peaks (872.54 nm, 1008.69 nm and 1138.62 nm) are 87.1%, 99.9% and 99.6%, respectively. The average absorption is 95.53%, including two perfect absorption peaks. Changing the structural parameters can affect its absorption peaks and resonant wavelengths. At the same time, due to the high symmetry of the absorber, it is not sensitive to the polarization angle and incident angle. Whether in the TE mode or the TM mode, the absorber at a wide incident angle (0-60°) also exhibits good operating angle polarization tolerance. Therefore, the perfect metamaterial absorber we designed can be widely used in sensing.